LAS RELACIONES DE PODER DESDE UNA EPISTEMOLOGIA SISTÉMICA - Christiansen, María (European Scientific Journal, ESJ, 2012)
The understanding of the concept of power in the social sciences and in the field of mental health means adopting certain epistemological positions which are not always explicit. Gregory Bateson referred disparagingly to the indiscriminate use of the idea of power, considering it a metaphor based on a epistemological error. His criticism was directed primarily to the linear, essentialist and simplificante approach that has prevailed in multiple scientific trends. In this article I examine their arguments and propose a bailout of the idea of power that does not fall into the epistemological vices reported by Bateson. Thus I explore two proposals from different disciplinary sources and apparently disconnected: the systemic psychotherapeutic model (influenced by Batesonian theories) and political science research by Pilar Calveiro. In both cases, although separate paths, we arrive at an antiessentialist, recursive, dialectical, ecological and relational conception about power. Furthermore, interdisciplinary dialogue records it fertility.